PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUASAN PELANGGAN PADA BIRO JASA LO ISE KABUPATEN ASAHAN - Handri, May (Fakultas Ekonomi Universitas Almuslim Bireuen, 2022)
The purpose of this research is to determine Service Quality, Price and Customer Satisfaction of the Asahan Regency Loise service bureau. The method used in this research is descriptive method, this type of research is quantitative data, primary data obtained through questionnaires. The population in this study was all 73 employees in the company. The sample used is a saturated sampling technique where the entire population will be used as a sample. The analysis technique used is multiple linear analysis. Test results show that the variables of service quality and price have a positive and significant effect on customer satisfaction at the lo ise service bureau in Asahan Regency.